Assessing agricultural commercialization and rural infrastructure development in rural Southwestern Nigeria: evidence from smallholder cassava farmers - Olutosin Ademola OTEKUNRIN (Acta Agriculturae Slovenica)
This study assessed agricultural commercialization and rural infrastructure development of smallholder cassava farmers in rural Southwestern Nigeria. The study was conducted in Nigeria with cross-sectional data collected from 352 smallholder cassava farmers. Crop commercialization index (CCI) was used to compute each farmer’s CCI and categorized into four levels while ordered logit model was employed to analyze the determinants of agricultural commercialization of cassava farmers in the study areas. Availability of some important rural infrastructures were assessed across cassava farmers’ commercialization levels. The results revealed that 13.1 % of cassava farmers did not participate in the sale of cassava roots while 86.9 % of them participated actively in the output market. The mean and maximum CCI in the study areas was 59.1 and 95.5 respectively. The results also showed that less than 40 % and 20 % of cassava farmers in all commercialization levels had access to electricity and piped water respectively. The ordered logit regression analysis indicated that age, transport cost, cassava marketing experience, and distance to market were among the determinants of agricultural commercialization. Therefore, stakeholders should expedite policy actions capable of promoting rural infrastructure development that will enhance agricultural production, marketing and improve the quality of life of rural farming communities.